(3TQM GddeYs - (3CHhGdbGSe YHO GdhGMO Hf Ydj Hf YeQ Hf ESMGb Hf EHQGgje GdCSOj GdYcHQj GdeYQha HGHf HQgGfs; (3GHf Lfj , CHh GdaJM YKeGf Hf Lfj GdehUdj, GHf Lfj,J (B392 (3g` s ((3eMeO Hf MUjf Hf LeghQ Hf jhSa GdhGSWi GdgeGej s)
(3ChdgG (B:s
(3bGd GdTjN CHhGdbGSe YHOGdhGMO GdfMhjhf LfS JMJg KdGKI CfhGY(B: (3eOfjhf, chajhf, HUQjhf s
(3BNQgG (B:s
(3ef jbhd(B: (3GdYdI aj EeGdJgeG CfgeG GSeGf ZjQ UaI, aCejdG JTHjgkG HMGQK hYGQe heGdc CYdGekG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HChdgG JedcGJ CbOegG HJGQjN (B964(3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs